Parallelisms & Lie Connections - Blázquez-Sanz, D.; Casale, G. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
The aim of this article is to study rational parallelisms of algebraic varieties by means of the transcendence of their symmetries. The nature of this transcendence is measured by a Galois group built from the Picard-Vessiot theory of principal connections.